Exchange interactions of ions - V. Likodimos; Guskos, N.; Wabia, M.; Typek, J. (Physical Review B - Condensed Matter and Materials Physics, 1998)
The EPR spectrum of (Formula presented) ions in (Formula presented) 0.5) is studied as a function of temperature. In the oxygen-deficient superconducting phase, the (Formula presented) EPR spectrum comprises a broad EPR line described by a rhombic g tensor and anisotropic linewidths along the principal axes. Analysis of the EPR linewidth provides an estimate for the effective isotropic exchange interaction, (Formula presented) between (Formula presented) ions, indicating that the magnetic ordering of the (Formula presented) sublattice is determined by the interplay between the short-range exchange interactions and the long-range dipole-dipole interactions. © 1998 The American Physical Society.